Pengaruh National Rifle Association Dalam Penolakan Arms Trade Treaty Di Amerika Serikat - Raditia Sapta Candra (HI 16 UMY 095, 2016)
*95 Violation of human rights, and crimes which happened around the world can be traced back to misuse of arms. Based on that, United Nations formulate a treaty that can regulate and control the trade, distribution, and use of these weapons. The United Nation’s Arms Trade Treaty seeks to establish the highest possible common international standards for regulating the international trade in conventional arms, prevent and eradicate the illicit trade in conventional arms and prevent their diversion for the purpose of contributing to international and regional peace, security and stability. The member states of United Nations are mostly in favor for such treaty, but unfortunately there are also some states that reject to ratify the treaty, including United States of America. This article will attempt to explain the reason of United States of America rejection of the Arms Trade Treaty. Keywords: arms, trade, treaty, interest group, foreign policy